2007
DOI: 10.1007/s10646-007-0173-x
|View full text |Cite
|
Sign up to set email alerts
|

Organophosphorous insecticides as herbicide synergists on the green algae Pseudokirchneriella subcapitata and the aquatic plant Lemna minor

Abstract: Models proposed for risk assessment of chemical mixtures assume no interactions between the chemicals. There are, however, studies indicating that some organophosporous insecticides can inhibit the detoxification of other chemicals in plants thereby enhancing their effect. The present study investigates whether interactions between selected organophosporous insecticides and herbicides can take place in the aquatic algae Pseudokirchneriella subcapitata and the aquatic macrophyte Lemna minor. For both species bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 38 publications
1
23
0
2
Order By: Relevance
“…A significantly lower toxicity than expected was also observed in a mixture of glyphosate and the organophosphorous insecticide chlorpyrifos applied at field recommended doses to B. napus (Martin and Ronco 2006). Antagonism was also detected in a work dealing with the joint effects of organophosphorous insecticides and herbicides on the green algae Pseudokirchneriella subcapitata and aquatic plant Lemna minor (Munkegaard et al 2008). In the work previously cited, it was concluded that the majority of mixtures tested resulted in antagonism, and no synergism was registered.…”
Section: Mixturementioning
confidence: 72%
See 1 more Smart Citation
“…A significantly lower toxicity than expected was also observed in a mixture of glyphosate and the organophosphorous insecticide chlorpyrifos applied at field recommended doses to B. napus (Martin and Ronco 2006). Antagonism was also detected in a work dealing with the joint effects of organophosphorous insecticides and herbicides on the green algae Pseudokirchneriella subcapitata and aquatic plant Lemna minor (Munkegaard et al 2008). In the work previously cited, it was concluded that the majority of mixtures tested resulted in antagonism, and no synergism was registered.…”
Section: Mixturementioning
confidence: 72%
“…Organophosphorous insecticides, like dimethoate, are known to inhibit the cytochrome P450 in terrestrial plants (Biediger et al 1992) which is known to play an important role in detoxification processes of several xenobiotics in plants (Munkegaard et al 2008). It also has been described that glyphosate inhibits the cytochrome P450 enzyme of wheat plants, which will increase the proportion of toxic molecules reaching the target site (Xiang et al 2005).…”
Section: Mixturementioning
confidence: 99%
“…It is known that mixtures of pesticides can provoke higher than expected impairment (synergism); so that this is one of the hypotheses raised here. Organophosphorous (OP) insecticides, like CPF, have been reported as plant cytochrome P450 monooxigenases inhibitors in terrestrial plants (Munkegaard et al 2008). Cytochrome P450 monooxigenases are known to play a role in the detoxification processes of xenobiotics and degrading pesticides in higher plants, so it is likely that the degradation of xenobiotics follow similar paths in algae (Munkegaard et al 2008) and a potential inhibition of P450 by OP insecticides in algae could increase its sensitivity to herbicide exposure.…”
Section: Discussionmentioning
confidence: 99%
“…A small number of studies have reported the potential threat to macrophytes exposed to pesticide mixtures in aquatic model ecosystems (Fairchild et al, 1994;Lytle & Lytle, 2002Wendt-Rasch et al, 2004). Recent laboratory studies with the standard OECD plant species Lemna minor addressed the joint toxicity of pesticides by applying the two common models of mixture toxicity: concentration addition (CA) and independent action (IA) (Belz et al, 2008;Cedergreen et al, 2007a, b;Munkegaard et al, 2008). The concept of CA is based on the assumption that any component of a mixture can be replaced by another without altering the overall effect of the mixture, and applied for toxicants with similar molecular target sites (Loewe & Muischnek, 1926).…”
Section: Introductionmentioning
confidence: 99%